Backlash : the Reappearing of a Vanished Marshall - Škrbić Alempijević, Nevena; Hjemdahl, Kirsti Mathiesen (2005)
The authors are dealing with the contemporary celebration of the Youth Day, the former Yugoslav holiday, and with other socialist icons from the perspective of the Croatian post-socialist society. They conclude that althrough the narratives generally cherished during the communist regime have been suppressed from all the visible strata of collective memory, recognizable topos, dates and figures still remain important in personal life histories, and the experience of individual remembrance.
Projekt MZOS
ENG